An Analysis on Code–switching in Rachel Goddard’s Youtube Channel - Dharmayanti, Ni Luh Putu Diah Ayu Sri Dharmayanti Diah (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
Code-switching is the use of two different languages in the same utterance, either between turns or inside a single expression or sentence. The purpose of this study was to identify the types of code-switching and the function of code-switching as it appeared in Rachel Goddard's videos. This study focused only on Indonesian to English code-switching. The data were taken from one of makeup videos of Rachel Goddard YouTube channel. The method used in this study was qualitative research and the technique to collect the data was the documentation method. The main theory used in this study was the theory from Hoffman (1991) and the supporting theories of this study were the theory from Apple and Muysken (1987). The result of the analysis showed that there are ten (10) sentences of intra-sentential code-switching and three (3) sentences of inter-sentential code-switching. Some data found contained poetic and phatic function.